Improved hydrodynamic performance of an OWC device based on a Helmholtz resonator. (15th June 2023) - Medina Rodríguez, Ayrton Alfonso; Trivedi, Kshma; Koley, Santanu; Oderiz Martinez, Itxaso; Mendoza, Edgar; Posada Vanegas, Gregorio; Silva, Rodolfo
Abstract: A numerical assessment was made of the hydrodynamic performance of a fixed Oscillating Water Column (OWC) device based on a Helmholtz resonator under regular and random wave conditions. The associated boundary value problem (BVP) was solved using the multi-domain three-dimensional boundary element method (BEM). Two configurations of the OWC device were evaluated: cylindrical and rectangular, and the effect of the neck design on the hydrodynamic performance for each was studied under regular wave conditions. Then, specific chamber configurations are selected to analyse their annual average plant efficiencies under the sea conditions of three sites that are suitable for OWC installation. The results showed that changing the neck parameters can significantly improve the hydrodynamic efficiency of the OWC device for various wave periods. Furthermore, the yearly average plant efficiency might be negatively impacted by low turbine damping, and a rise in air column height does not always correspond to a decrease in efficiency, as this can also depend on the neck submergence. Finally, it was found that the Helmholtz resonator-based OWC device can perform well in terms of power conversion for the relatively higher wave periods commonly found at the sites of interest. Highlights: The OWC device resonates at a frequency determined by the dimensions of the neck. The hydrodynamic efficiency with a shorter-breadth OWC was significantly improved. This type of OWC device's power conversion may be suitable for real-world sea states.